The international diffusion of RDA: a wide overview on the new guidelines - Carlo Bianchini; Mauro Guerrini (JLIS.it, 2016)
This issue of Jlis.it is focused on RDA, Resource Description and Access. In light of increasing international acceptance of this new cataloging content standard, the editors of Jlis.it wish to capture the background of how RDA came to be and the implications of its implementation at this time. This special issue offers a wide overview on the new guidelines from their making to their spreading around the world.